PERBEDAAN JUMLAH ABSOLUT NEUTROFIL DAN MONOSIT PADA DERAJAT CEDERA FRAKTUR TEBRUKA DI RSUD ULIN BANJARMASIN Tinjauan Penelitian Analitik Retrospektif Tahun 2019-2022 Berdasarkan Klasifikasi Gustilo-Anderson - Fadhillah, Muhammad Naufal; Putera, Husna Dharma; Hendriyono, Fransiscus Xaverius (Homeostasis, 2023)
Open fracture is a condition of serious fracture injury where there is a connection between the fracture fragments and the outside world. Traffic accidents are the most frequently reported cause of open fracture cases. Injured soft tissue will experience inflammation which causes increase in inflammatory cells present in the injured area. The variation in the number of leukocytes is related to the severity of the patient's injury. Neutrophils and monocytes are the first types of leukocytes present in the injured area to carry out phagocytosis. This study aims to analyze the difference of the absolute number of neutrophils and monocytes in the degree of open fracture injury based on the Gustilo-Anderson classification at Ulin Hospital, Banjarmasin in 2019-2022 as one of the biological parameters for the initial assessment of the clinical condition of open fracture patients. This study used an analytic observational method with a retrospective cross sectional approach. The sampling technique uses the total sampling method. Data were obtained for 32 subjects for each absolute variable neutrophil and monocyte with 1 subject on type I, 6 subjects on type II and 25 subjects on type III. The results of the comparative analysis test between the degrees of injury obtained p = 0.245 for absolute neutrophils and p = 0.558 for absolute monocytes. The conclusion of this study was that there was no significant difference in the absolute number of neutrophils and monocytes between the degrees of open fracture injury at Ulin Hospital, Banjarmasin in 2019-2022 based on the Gustilo-Anderson classification.